A study on English Substitutions of Synonym with reference to the Vietnamese equivalents / Trần Hà Anh; NHDKH Assoc. Prof. Dr. Lê Văn Thanh - Trần, Hà Anh
This article is an attempt to identify substitutions of synonym in both English and Vietnamese as a discourse cohesive device. Both quantitative and qualitative approaches are used in the thesis. Besides, the thesis is carried out based on the research methods such as statistical research, methodology description, analysis and synthesis methods, comparing and contrasting methods. With the corpora from stories and novels, the study classifies substitution of synonym in English and Vietnamese into three types: dictionary substitution of synonym, temporary substitution of synonym and descriptive substitution of synonym. Then, the study explores the linguistic features of these types of substitution of synonym in English and Vietnamese in term of syntax and semantics. This aims to help learners to identify the type of vocabulary and semantics common synonyms used in rather a synonym, at the same time learners can have a better use of synonyms as a way of forming cohesion. The findings of the study show frequency and diversity in the relationship of the emergence of substitute synonyms in English and Vietnamese. In addition, on the basic of the findings, some suggestion are put forward to help Vietnamese teachers and learners of English master substitution of synonym.